Anti‐inflammatory and immunomodulatory effects of Biodentine on human periapical lesion cells in culture. (24th July 2020) - Eraković, M.; Duka, M.; Bekić, M.; Tomić, S.; Ismaili, B.; Vučević, D.; Čolić, M.
Abstract: Aim: To evaluate the effect of Biodentine eluate on cytotoxicity and production of pro‐ and anti‐inflammatory cytokines and osteodestructive/osteoprotective cytokines in cultures of human periapical lesion cells. Methodology: Conditioned Biodentine Medium (CBM) was prepared according to ISO 10993‐12, by incubating Biodentine in RPMI medium (0.2 g mL −1 ) for 3 days at 37 °C. CBM contained both released microparticles and leachable soluble components. Inflammatory cells were isolated from 22 human periapical lesions after apicectomy or tooth extraction, by collagenase/DNase digestion, and cultured in several dilutions of CBM. The composition of periapical lesion cells was determined by morphological criteria, cytotoxicity was quantified by MTT and flow cytometric apoptosis/necrosis assays, whereas the levels of produced cytokines in cell culture supernatants were measured by flow cytometry and ELISA. Student t‐test and Friedman test with Dunn's post‐test were used for comparison of parametric and nonparametric variables, respectively. Results: Undiluted (100%), 75% and 50% CBM were cytotoxic for periapical lesion cells due to induction of both necrosis (100% CBM) and apoptosis (75% and 50% CBM). Noncytotoxic concentrations of CBM (25%) inhibited the production of pro‐inflammatory cytokines: TNF‐α, ( P  < 0.005); IL‐1β ( P  < 0.01); IL‐6 ( P  < 0.005) and chemokines IL‐8: ( P  < 0.005); MCP‐1 ( P  < 0.005), stimulated the production of anti‐inflammatory cytokine (IL‐10; P  < 0.005), Th2 cytokines: IL‐4, IL‐5 and IL‐33 (all P  < 0.01), and IL‐17A ( P  < 0.01). The concentration of CBM (12.5%) inhibited the production of IL‐6 ( P  < 0.05), IL‐8 ( P  < 0.01) and MCP‐1 ( P  < 0.005) and augmented the production of IL‐10 ( P  < 0.05). No significant effects on Th1‐related cytokines (IFN‐γ and IL‐12) and IL‐23 were detected with 25% and 12.5% CBM concentrations. Both CBM concentrations inhibited the production of osteolytic receptor activator of nuclear factor kappa‐Β ligand (RANKL), dose dependently ( P  < 0.005 and P  < 0.01, respectively). Higher CBM concentrations decreased RANKL/osteoprotegerin (OPG) ratio ( P  < 0.05), without significant influence on the levels of osteoprotective OPG. Conclusion: Biodentine possesses immunomodulatory properties by suppressing pro‐inflammatory and augmenting anti‐inflammatory cytokines. Together with the reduction of osteodestructive mediators, this novel root‐end filling cement could be beneficial for healing and bone reparation after the surgical treatment of periapical lesions.